Photographing Ganjar Pranowo's Efforts to Build Personal Branding Through a Multi-Platform Strategy Perspective on Social Media - Arum Martikasari (Sospol : Jurnal Sosial Politik, 2023)
This study seeks to describe the use of the multi-platform strategy concept used by Ganjar Pranowo in building his personal branding. The method used in this study is a literature study with data sources in the form of screenshots from Ganjar Pranowo (Ganjar) official account uploads on social media as primary data and textbooks, journals, scientific articles, literature reviews containing the concepts studied as secondary data. Ganjar's efforts in building his personal branding will be dissected first using the concept of Brand Archetypes and then discussed based on three points of view to see the multi-platform strategy applied. Based on the analysis that has been done, it can be concluded that Ganjar uses at least 2 main strategies in building his personal branding. The first is to choose and build his persona as a regional leader as well as a public servant who has the archetype characters of The Care Giver, The Jester and The Regular Guy. Second, these three archetypes appear consistently through multi-platforms on social media using Facebook, Twitter, Instagram and Youtube.